Gas phase detection and rotational spectroscopy of ethynethiol, HCCSH. (18th June 2019) - Lee, Kin Long Kelvin; Martin-Drumel, Marie-Aline; Lattanzi, Valerio; McGuire, Brett A.; Caselli, Paola; McCarthy, Michael C.
ABSTRACT: We report the gas-phase detection and spectroscopic characterisation of ethynethiol ( HCCSH ), a metastable isomer of thioketene ( H 2 C 2 S ) using a combination of Fourier-transform microwave and submillimetre-wave spectroscopies. Several a -type transitions of the normal species were initially detected below 40 GHz using a supersonic expansion-electrical discharge source, and subsequent measurement of higher-frequency, b -type lines using double resonance provided accurate predictions in the submillimetre region. With these, searches using a millimetre-wave absorption spectrometer equipped with a radio frequency discharge source were conducted in the range 280–660 GHz, ultimately yielding nearly 100 transitions up to r R 0 ( 36 ) and r Q 0 ( 68 ) . From the combined data set, all three rotational constants and centrifugal distortion terms up to the sextic order were determined to high accuracy, providing a reliable set of frequency predictions to the lower end of the THz band. Isotopic substitution has enabled both a determination of the molecular structure of HCCSH and, by inference, its formation pathway in our nozzle discharge source via the bimolecular radical-radical recombination reaction SH + C 2 H, which is calculated to be highly exothermic (−477 kJ/mol) using the HEAT345(Q) thermochemical scheme. GRAPHICAL ABSTRACT: